Teacher Education: adaptability of education professionals and the use of digital technologies in the face of COVID-19 Pandemic crisis (Research, Society and Development, 2021)
This article aims to analyze the implications of the COVID-19 pandemic in the teaching practice of education professionals and their adaptability to new digital teaching technologies. In this sense, we sought to answer the following questions: How will the schools and responsible agencies (Ministry of Education and State Education Council) solve the scenario of education in the face of the pandemic installed in Brazil? What tools and/or methodologies can be used to avoid harming students in this critical period installed in Brazil? To this end, a theoretical essay was carried out with the authors who discuss the pandemic crisis, the use of TDICs in education and the need for continuing teacher education: Santana & Sales (2020), Pretto et al. (2020), Nascimento & Prattes (2020), Heinsfeld & Pischetola (2019), Arruda (2020), Moran (2015), Cavallo et al. (2019), among others. It was found that the agencies mentioned above allowed the change from classroom to remote classes, however, teachers, students and families were not prepared to face the crisis that was installed by COVID-19. Thus, it is necessary to continue the training of teachers so that they can develop skills and abilities to face future problems such as what happened with this pandemic. Especially because to continue teaching it is necessary to continue learning, according to the words of Paulo Freire.